A Skills beyond School Review of England - Musset, Pauline (OECD Publishing, 2013)
This book examines vocational education and training programmes in England, including coverage of how they are changing, how they are funded, how they are linked to academic and university programmes and how employers and unions are involved
Keywords: Education